2009
DOI: 10.4094/jkachn.2009.15.4.359
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Body Image, Intentional Caloric Restriction and Physical Manifestations of Unbalanced Nutrition according to Body Mass Index in Fifth and Sixth Grade Elementary School Students

Abstract: This study was done to identify perceived body image, intentional caloric restriction and physical manifestations of unbalanced nutrition according to the Body Mass Index (BMI) in elementary school students. Methods: The research design was a cross-sectional descriptive study. Data collection was done by using a structured questionnaire that consisted of 34 items. Participants were 151 students in 5th and 6th grades of elementary schools in Gangwon province. Frequency and percentage, one-way ANOVA, and 2-test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…A study in which the identical instrument was used to determine CRE of fifth-and sixth-graders obtained a similar result: 19.59 in the BMI-U group, 21.23 in the BMI-N group, and 23.83 in the BMI-O group [10]. A study in seven-to twelve-year-old children also found that the higher BMI, the higher level of restraint of eating [33].…”
Section: Bmi Bip Cre and Depression Of Subjectsmentioning
confidence: 48%
See 3 more Smart Citations
“…A study in which the identical instrument was used to determine CRE of fifth-and sixth-graders obtained a similar result: 19.59 in the BMI-U group, 21.23 in the BMI-N group, and 23.83 in the BMI-O group [10]. A study in seven-to twelve-year-old children also found that the higher BMI, the higher level of restraint of eating [33].…”
Section: Bmi Bip Cre and Depression Of Subjectsmentioning
confidence: 48%
“…At the time of developing this instrument, Cronbach's α=.94 for reliability of all of the 32 items and Cronbach's α=.87 for reliability of the CRE scale. A previous study only using a CRE scale in elementary school children (10) found that Cronbach's α=.81 for reliability of the instrument. As for reliability of this scale in this study, Cronbach's α=.89.…”
Section: Cognitive Restraint Of Eating (Cre)mentioning
confidence: 99%
See 2 more Smart Citations
“…Further, nutrient inadequacy or unhealthy dietary patterns in childhood may be associated with adverse health outcomes during childhood and adolescence and can even persist into adulthood (B. H. Kim & Choi, 2009). Currently, many schools offer nonnutritional items that can easily be obtained from soda and snack machines (Shariff et al, 2008), lowering the likelihood of children eating fruits and vegetables, especially if they are not available options.…”
Section: Discussionmentioning
confidence: 99%